Human Body in the Flow of History (about the Thesis of Justina Kozakaitė „Traumas in 13th–18th Century Lithuania Based on Bioarchaeological Data“) - Šipelytė, Monika (Lietuvos istorijos studijos, 2018)
[text in Lithuanian]
Keywords: none